Objective assessment of nonadherence and unknown co-medication in hospitalized patients - Carow, Florentine; Rieger, Karin; Walter-Sack, Ingeborg; Haefeli, Walter E. (European journal of clinical pharmacology, 2012)
PurposeThe intake of medications (drugs) without the knowledge of the treating physician (unknown co-medication) and nonadherence strongly influence drug safety. The aim of our study was to objectively assess unknown co-medication and nonadherence in hospitalized patients by screening urine for a large number of drugs using highly sensitive full scan gas chromatograpy/mass spectrometry (GC/MS). Secondary objectives were to determine the relationship of co-medication and nonadherence to the number of drugs prescribed and to compare history-taking by a pharmacist versus a physician.MethodsIn 152 patients, the drug histories taken by physicians, patients’ self-reported adherence, and information compiled during as many as three structured interviews conducted by a trained pharmacist on days 1-2, 3-4, and 7-11 of the hospital stay were compared with the GC/MS results from urine samples collected after each interview.ResultsIn the interviews performed by the pharmacist, 235 additional drugs were identified that were not documented in the chart. Of all the drugs indicated in any interview, 16.9% were identified only by the physician, 24.1% only by the pharmacist, and 59% by both. Overall, in 78% of the patients at least one additional drug was identified by urine screening. The findings suggest overall nonadherence to at least one drug in 13.0% of patients on admission and in 23.3% of patients at any time during hospitalization. Nonadherence was less frequent for critical dose drugs and correlated with the number of prescribed drugs.ConclusionsThe drug history among hospitalized patients is often incomplete, and nonadherence and unknown co-medication are alarmingly frequent. This lack of knowledge might impact the overall success of drug therapies in the hospital setting.